2015
DOI: 10.3109/02652048.2015.1073392
|View full text |Cite
|
Sign up to set email alerts
|

Development of chitosan–pullulan composite nanoparticles for nasal delivery of vaccines: optimisation and cellular studies

Abstract: Nasal immunisation with nanoparticles has already shown promising results. In this study, nanoparticle composites carrying BSA for nasal vaccination prepared using electrostatic interaction process between polycation N-trimethyl chitosan chloride (TMC), chitosan glutamate (CG), chitosan chloride (CCl) and polyanion carboxymethyl pullulan (CMP). A mass ratio of 2:1 for TMC-CMP combination produced stable nanocarriers. For CCl-CMP and CG-CMP formulations needed a mass ratio of 3:1. Loading efficiency was >90% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Much stronger complexation between N ‐trimethyl CS chloride and CMP resulted in smaller particle size when compared with CS salts. In mouse macrophages (J774A.1), the highest uptake efficiency was found with N ‐trimethyl CS chloride–CMP composite particles after 2‐hrs incubation which could be explained by their smaller dimension and more narrow particle size distribution .…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 94%
See 2 more Smart Citations
“…Much stronger complexation between N ‐trimethyl CS chloride and CMP resulted in smaller particle size when compared with CS salts. In mouse macrophages (J774A.1), the highest uptake efficiency was found with N ‐trimethyl CS chloride–CMP composite particles after 2‐hrs incubation which could be explained by their smaller dimension and more narrow particle size distribution .…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 94%
“…Carboxymethyl pullulan (CMP) was reported as a polyanion for the first time to prepare composite nanoparticles for delivery of vaccines . The process of carboxymethylation enhances solubility of pullulan in cold water, and adding carboxylate groups along the polymer backbone provides a negative charge which is then allowed to react with polycations to form stable nanocomplexes during polyion complexation .…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…separation of particles, reducing the extent of aggregation caused by Van de Waals interactions. 29 In this study, microsphere formulations resulted in positive zeta potential value of between +16.5 mV and +18.7 mV; the polymer:TPP mass ratio did not significantly influence the surface charge of the microspheres. Particle morphology was evaluated by SEM.…”
Section: In Vitro Studies Resultsmentioning
confidence: 52%
“…Prepared nanoparticles showed good drug release. Cevher and coworkers synthesized nanoparticles by electrostatic interaction between negatively charged CMP and positively charged CS derivatives (N‐trimethyl CS chloride, CS glutamate, CS chloride) and reported that a significantly low cytotoxic activity in respiratory cells (Calu‐3 cells) than that of the CS derivatives, alone. Also highest uptake efficiency was found with N‐trimethyl CS chloride−CMP composite particles after 2‐hrs incubation which was due to their smaller size and narrow particle size distribution.…”
Section: Pullulanmentioning
confidence: 99%